Objets connectés - Aymeric Bouchereau; Ioan Roxin (Centre National d'Enseignement à Distance, 2020)
The evolution of information and communication technologies is leading to the development of an Internet of Things that is transforming our interactions with objects and changing the way we learn and be informed. Extending the human perception of physical phenomena and facilitating experimentation, connected devices can play a catalytic role in scientific mediation. Their use in science education introduces two activities that combine face-to-face and distance learning: in situ experimentation and remote laboratory. We have designed four learning devices for the understanding of photometric quantities and conducted an experiment to study the effects and challenges of the use of connected devices. The results show that they bring closer theory and practice and that they imply the adaptation of scientific knowledge.